INTER-PREDICATE ADHESION PROCESS OF VERBAL SUFFIX ON PRINCIPLE OF GRAVITATION ONTO PREDICATE - Turgay SEBZECİOĞLU (Fırat University, 2019)
Predicate, which is center of sentence, pulls lexical and grammatical morphemes out of its domain toward own with the verb which means its nucleus. Thus, it forms a gravitational field which is bended towards its own field. However some of morphemes are effected from gravity force of predicate less, some of them is affected more. Instant cognivite operations might be observed such as stylistic preferences and movement on the process of gravitation. But these process does not come out with adhesion of morphemes to the inter-predicate field permanently. There is a strong gravitation need on inter-predicate field. Adhesion, which is composed strong gravitation result, has a grammatical means systemic change and it requires diachronich process. Adhesional morphemes to the inter-predicate field means that it has gained categorise features appopriate to the predicate as a result of genetic agreement through its historical process. For this reason, adhesional morphemes are exposed to predicate attraction intensenly. It is able to complete process of gravitation towards inter-predicate field due to integration and adhesional properties. In this study, strong or weak, all these following gravitation process is legislated by the name of Principle of Gravitation onto Predicate. In Tukish language, some of verbal suffixes (such as infinitive, participle and gerund) which provide Condition of Inter-Predicate Adhesion carry obvious effect of this principle on bound grammatical morphemes. It is possible to observe the bending process towards to the predicate on both diachronic evolution and synchronic tendency of verbal suffix. Some of verbal suffixes turn into suffixes of mood, tense and aspect with genetical adaptation in which clause; some of them form grammatical construction on the purpose of description. In this way, these verbal suffixes could achieve inter-predicate adhesion. It appears that some of verbal suffixes are about at the end of inter-predicate adhesion process from their being lexical tendency. In this study, it has been tried to explain that these all observations in associated with verbal suffix under the skin of Principle of Gravitation onto Predicate.